An ecologically sensitive measure of executive cognition (the Breakfast Task) improves prediction of functional outcome in schizophrenia. Issue 5 (3rd September 2022) - Pishdadian, Sara; Parlar, Melissa E.; Heinrichs, R. Walter; McDermid Vaz, Stephanie
Abstract: Previous work has found that the Breakfast Task (BT), a computerized, ecologically informed executive ability measure, is sensitive to group differences in aging, acquired brain injury, and Parkinson's disease. We investigated whether this measure improves the prediction of functional status over and above standard measures of general intellectual ability, relationship perception, life skills, and symptom severity in individuals with schizophrenia. Regression analyses were conducted to evaluate the joint and incremental validity of the BT in predicting functional disability scores on the World Health Organization Disability Assessment Scale (WHODAS 2.0). Analyses with combined patient ( n = 25) and control ( n = 32) participants showed that participant status (patients versus control) was the only significant predictor of functional outcome. However, in the patient data, the proportion of variance accounted for improved significantly (model R 2 of 4% vs. 25%) when BT scores were added to a model containing clinical (Brief Psychiatric Rating Scale), social (Relationships Across Domains), intellectual (Wechsler Abbreviated Scale of Intelligence), and life skills (Canadian Objective Assessment of Life Skills) measures. Results suggest that the BT, a tool that captures complex executive functioning, improves the prediction of disability in patients with schizophrenia and has potential assessment applications.